2001
DOI: 10.1080/02724990143000045
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in human olfaction: Between evidence and enigma

Abstract: The sex of individuals plays an important part in determining their olfactory abilities, with females generally being superior to males. The present review examines the way in which sex differences influence sensitivity, identification, familiarity, and recognition of odours. It also examines whether sex differences are more pronounced with some odours than others, and how sex differences are affected by the manner of testing. Two different explanations for the superiority of females over males in olfaction ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
152
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(169 citation statements)
references
References 68 publications
10
152
1
Order By: Relevance
“…There is a relatively robust body of evidence that women tend to outperform men in various olfactory-related tests (for reviews see Brand and Millot 2001;Doty and Cameron 2009) and report a greater significance ascribed to olfaction (Havlicek et al 2008). On the other hand, sex differences tend to be smallest in young adults (Doty 1992) and have been reported to be restricted to the fertile phase of the menstrual cycle (Navarrete-Palacios et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…There is a relatively robust body of evidence that women tend to outperform men in various olfactory-related tests (for reviews see Brand and Millot 2001;Doty and Cameron 2009) and report a greater significance ascribed to olfaction (Havlicek et al 2008). On the other hand, sex differences tend to be smallest in young adults (Doty 1992) and have been reported to be restricted to the fertile phase of the menstrual cycle (Navarrete-Palacios et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…After puberty, girls have better olfaction abilities than boys. 17,18 From the age of ϳ40 years, olfaction abilities decrease, which partly explains anorexia in the elderly. 18 The role of olfaction in adults is likely involved in several fields, such as appetite, emotional memory, and sexual bonding.…”
mentioning
confidence: 99%
“…Overall, studies show that females outperform men in most olfactory tasks (see Brand & Millot, 2001 for a review). However, for odor sensitivity tasks (i.e., threshold), the pattern of findings is conflicting (Brand & Millot, 2001).…”
Section: Sexmentioning
confidence: 99%
“…Overall, studies show that females outperform men in most olfactory tasks (see Brand & Millot, 2001 for a review). However, for odor sensitivity tasks (i.e., threshold), the pattern of findings is conflicting (Brand & Millot, 2001). The National Geographic Smell Survey (1989) conducted by Wysocki and Gilbert revealed that women rated odors as more intense and also exhibited a higher detection accuracy.…”
Section: Sexmentioning
confidence: 99%